Rapid emergence of dolutegravir resistance on second-line dolutegravir-based ART - Kirusha Naidoo; Richard J. Lessells; Jienchi Dorward; Mahomed Y.S. Moosa; Yukteshwar Sookrajh; Pravi Moodley; Paul K. Drain; Nigel Garrett (Southern African Journal of HIV Medicine)
The integrase strand transfer inhibitor, dolutegravir (DTG), is widely used in first- and second-line antiretroviral therapy (ART) regimens in South Africa. We describe an adult with virological failure on second-line tenofovir/lamivudine/dolutegravir (TLD2) and rapid emergence of DTG resistance within 3 months, while receiving rifapentine-based tuberculosis preventive therapy.